Gender-differences in Agro-Climate Information Services (Findings from ACIS baseline survey in Ha Tinh and Dien Bien provinces, Vietnam) - Smith, Abigail; Simelton, Elisabeth; Duong, Minh Tuan; Le Thi Tam; Coulier, Miguel (2017)
This brief summarized the baseline survey and the testing of different agro-advisories conducted in the Agro-Climate Information Services for women and ethnic minority farmers in South-East Asia (ACIS) project sites: Dien Bien and Ha Tinh provinces in Vietnam. The baseline survey gathered information on diverse aspects of livelihoods, food security, climate hazards and impacts, as well as access to and quality of weather and agricultural information. In a Participatory Scenario Planning (PSP) meeting, six samples of the agro-advisory developed in the project were tested by the men and women farmer respondents. Results show that men and women farmers’ needs and preferences must be considered in order to most effectively disseminate agro-climate information. The ways in which gender impacts farm-level adaptations and market transactions has implications for farm planning, managing, monitoring, and marketing of products. The study confirms the importance of considering gendered factors, among other, in climate information services.